Penjadwalan Pakan Dan Pengendalian Suhu Pada Kandang Babi Secara Otomatis Berbasis Arduino - Aloysius Gonzaga Lai Boro; Aries Boedi Setiawan; Wahyu Dirgantara (Muhammadiyah University, Sidoarjo, 2019)
he research was conducted on the pig farm owned by Mr. Santo, at the West Bandulan, Sukun Sub District of Malang in East Java province for 4 weeks (1 month). This research uses 4 pigs where 2 tails are fed automatically and the 2 tail still uses manual way. The purpose of this research is to provide farmers with information on the effects of feeding timely on the increase in pig weight. The method used is the experiment (experimental) consisting of 2 experiments that were first performed automatic feeding of 2 pigs that both feed manually against 2 pigs so as to find a comparison of The experiment. Looking at this, then the author devised a tool scheduling and automatic feeding of Arduino-based Mega 2560. With this tool, the author hopes to help pig farmers in increasing pig weights and relieve breeder's work. Thereby can improve the welfare of pig farmers. Results of the experiment showed the growth of pigs using the automated system better with the result 0.58 – 0.68 kg per day.